From Product to Relationship: A Service-Dominant Logic Approach to Gen Z Loyalty in Kopitiams - Setiadi, Deni; Rohman, Fatchur; Hapsari, Raditha Dwi Vata (Jurnal Aplikasi Manajemen, 2025)
The rapid proliferation of the coffee shop industry, coupled with the high mobility and exploratory nature of Generation Z students, presents a critical challenge for Kopitiam businesses in maintaining customer retention. Grounded in Service-Dominant Logic (SDL), this study aims to analyze the influence of personalized experience and food and beverage quality on customer loyalty, with brand trust serving as a mediating variable. This explanatory quantitative research collected data through a purposive sampling technique from 150 Generation Z university students in Malang City who had visited a Kopitiam at least twice within the last six months. Data were analyzed using Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The findings reveal a distinct dichotomy where personalized experience has a significant direct effect on enhancing customer loyalty, whereas food and beverage quality does not directly influence loyalty but is fully mediated by brand trust. This indicates that in a saturated market, product quality functions merely as a hygiene factor, while brand trust acts as the pivotal psychological axis for Generation Z customer commitment. The novelty of this study lies in positioning brand trust as a bridge between functional product value and relational experience within the Kopitiam cultural ecosystem. These findings imply that Kopitiam operators must shift their focus from mere menu innovation to "relationship engineering," prioritizing organic personal interaction and consistent operational standards to ensure long-term loyalty.